2019
DOI: 10.1186/s13104-019-4052-3
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ preferences towards learning resources and their study habits at King Abdulaziz University, Jeddah, Saudi Arabia

Abstract: ObjectiveThe purpose of the present study was to explore why our medical students are avoiding the study of professional textbooks. We conducted this study from 10th March to 15th May 2017 at the King Abdulaziz University (KAU), Jeddah, to investigate their preferences towards learning resources, their study habits and correlation of academic achievements as a result of these trends. A questionnaire was provided as a web link. The participants of the study included medical students and data was analyzed on SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
4
19
0
2
Order By: Relevance
“…Studies on medical students in Saudi Arabia also found that English language proficiency is related to avoidance of textbook reading as well as poor academic performance. 9 , 10 The availability of Internet facilities at the individual level also has a significant effect on student achievement. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on medical students in Saudi Arabia also found that English language proficiency is related to avoidance of textbook reading as well as poor academic performance. 9 , 10 The availability of Internet facilities at the individual level also has a significant effect on student achievement. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 The availability of Internet facilities at the individual level also has a significant effect on student achievement. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study from King Abdulaziz University (KAU) reported that students like medical websites, online textbooks, and journals. 1 The KAU students use online medical applications for their knowledge acquisition and to do their assignments, 2 and a significant number of medical students are addicted to their smartphones. 3 Blended learning (BL) is the integration of conventional face-to-face teaching with online content.…”
Section: Introductionmentioning
confidence: 99%
“…Subject matter mastery depends on students’ attitudes towards learning. 1 Jamil et al. (2019) state that certain instruction modalities, such as case-based learning (CBL) and problem-based learning (PBL), force medical students to open up their textbooks to gather required information.…”
Section: Introductionmentioning
confidence: 99%